Ethics in Indian materialist philosophy: in its social perspective - "Kar, Bijayananda" (Shimla, 2013)
The book is an analytical study of the major ethical and moral ideas in the history of Indian materialism and traces critically its trajectory through the early centuries to the modern age. Involving a detailed consideration of the primary sources, the book attempts to understand from the perspective of ethics and morality the ramifications of the major changes which have occurred in India, in the thinking on materialism. The book engages with the ideas of thinkers such as Carvaka, the classical writers such as Jayarasi Bhatta, Krsna Misra, and modern thinkers including M.N. Roy and Jawaharlal Nehru. It is expected to be well received both by the scholars and general readers.
Keywords: "Materialism, Philosophy, Ethics"